MACROMETRIC PARAMETERS OF THE STRUCTERES OF MEDULLA OBLONGATA IN THE PRENATAL PERIOD OF HUMAN ONTOGENESIS IN NORMAL AND MALFORMATION - Tikholaz, V.O.; Oniskova, O.V.; Yushchenko, L.O.; Skoruk, R.V.; Hordiichuk, O.O. (World of Medicine and Biology, 2019)
The article presents results of investigations of macrometric parameters of medulla oblongata in 230 human fetuses from 8-9 till 39-40 weeks in prenatal period of ontogenesis. The dimensions of the medulla oblongata and the sizes of the olives in different age groups in human fetuses without anomalies and in human fetuses with malformation were determined. Accelerated growth rate of all sizes of medulla oblongata and the sizes of the olives were found in different age groups in human fetuses.